An Equity Framework to Engage Community College Preservice Teachers in Black Liberatory Practices - Denise Farrelly; Joanna Maulbeck; Laura Scheiber (Northwest Journal of Teacher Education, 2023)
While representation of teachers of color remains startlingly low nationwide, it is critical to recognize that increasing diversity is not enough to increase access to an inequitable system. Centering the strengths of Black students, on both an individual and institutional level, through culturally and historically-responsive pedagogical and curricular practices is a crucial step toward equitizing the teaching workforce. Using a culturally and historically-responsive literacy (HRL) framework, we discuss and reflect upon practical classroom-based approaches to engage community college preservice teachers in responsive pedagogical practices that are aligned with the legacy of Black literary societies. The paper is divided into four sections, each one aligning with a layer of this equity framework. By reflecting on practices and experiences within our urban community college teacher education program, we share pragmatic strategies for centering Black liberatory practices with other scholar-practitioners in the field of teacher education, while simultaneously acknowledging pathways to improvement.